Occurrence and persistence of future atmospheric stagnation events - Horton, Daniel E. (2014)
Poor air quality causes an estimated 2.6 to 4.4 million premature deaths per year(1–3). Hazardous conditions form when meteorological components allow the accumulation of pollutants in the near-surface atmosphere(4–8). Global warming-driven changes to atmospheric circulation and the hydrological cycle(9–13) are expected to alter the meteorological components that control pollutant build-up and dispersal(5–8,14), but the magnitude, direction, geographic footprint, and public health impact of this alteration remain unclear(7,8). We utilize an air stagnation index and an ensemble of bias-corrected climate model simulations to quantify the response of stagnation occurrence and persistence to global warming. Our analysis projects increases in stagnation occurrence that cover 55% of the current global population, with areas of increase affecting 10 times more people than areas of decrease. By the late-21(st) century, robust increases of up to 40 days per year are projected throughout the majority of the tropics and subtropics, as well as within isolated mid-latitude regions. Potential impacts over India, Mexico, and the western U.S. are particularly acute due to the intersection of large populations and increases in the persistence of stagnation events, including those of extreme duration. These results indicate that anthropogenic climate change is likely to alter the level of pollutant management required to meet future air quality targets.